The application of chitosan in food-grade coatings to control Tyrophagus putrescentiae on dry-cured hams and the effects on sensory properties. (December 2021) - Shao, Wenjie; Campbell, Yan L.; Phillips, Thomas W.; Freeman, Charles; Kundu, Santanu; Crist, Courtney A.; Williams, J. Byron; Schilling, M. Wes
Abstract: The objective of this research was to evaluate if chitosan-containing food-grade coatings can control Tyrophagus putrescentiae growth without affecting the sensory attributes of dry-cured hams. Food-grade coating treatments included (1) 0.3% chitosan (CH), (2) 0.6% CH, (3) 0.3% CH + 10% propylene glycol (PG), (4) 0.3% CH + 1% xanthan gum (XG), (5) 0.3% CH + 1% XG + 10% PG, (6) 0.3% CH + 1% carrageenan (CG) + 1% propylene glycol alginate (PGA), and (7) 0.3% CH + 1% CG + 1% PGA + 10% PG. Each coating solution was coated on ham cubes (2.54 × 2.54 × 2.54 cm 3, n = 5/treatment) or infused in ham nets and dry-cured ham cubes were wrapped in the ham nets prior to inoculation with 20 adult mites. A randomized complete block design with three replications was utilized to evaluate the efficacy of treatments at controlling mite growth on dry-cured ham. When CH was mixed with XG (0.3% CH + 10% PG + 1% XG, and 0.3% CH + 1% XG) and infused into a net, fewer mites (15.7 and 21.0 mites) were on the ham cubes ( P  < 0.05) in comparison to the control (211.2 mites). Results indicate that CH has the efficacy to control mites since 1% XG alone did not control mite growth. Difference from control test results indicated that no sensory differences existed (NS) between CH-treated and control ham slices. The addition of chitosan coated nets helped control mite growth when used in conjunction with xanthan gum and propylene glycol and collectively may be useable as part of an integrated pest management plan for ham producers to control mites in their aging houses. Therefore, these coating solutions could be scaled up to evaluate their efficacy in ham aging houses. Highlights: Chitosan improved mite control in a 1% xanthan gum and propylene glycol coating. Chitosan did not control mites as a stand-alone treatment. The addition of chitosan did not affect the sensory attributes of dry-cured ham.